Psychological Problems in a Sample of Jordanian Healthcare Workers Involved in Caring for Patients With COVID-19: A Cross-Sectional Study - Alhalaiqa, Fadwa Naji; Khalifeh, Anas H.; Al Omari, Omar; Yehia, Dalal Bashier; Khalil, Malek Mohammad Hassan (Frontiers in Psychology, 2021)
Abstract Purpose: To explore psychological problems (stress, depression, and anxiety) and the level of resilience among frontline healthcare workers (HCWs) who provide care for patients with COVID-19. Additionally, we wanted to identify the correlation among these problems, resilience, and demographics of participants. We also explored the main predictors of stress, depression, anxiety, and resilience. Methods: A descriptive cross-sectional correlational design and convenience sample technique were used to collect data from active Jordanian HCWs who directly deal with patients suspected or confirmed to be infected with COVID-19 and work at healthcare facilities in Jordan. Data were collected by using online questionnaires about participants’ demographics, stress, anxiety, depression, and resilience. Results: Data were collected from 225 HCWs. Their mean age was 31.17 years (SD= 6.8). All participants perceived different levels of stress, with most perceiving exposure to a high level of stress (distress) (46.2% with low level and 53.8% with high level of stress); around half of them (52.9%; n=119) reported a high level of anxiety, and more than half (66.2%; n=149) had a high level of depression. Additionally, an increased anxiety and depression level was significantly associated with decreased resilience and increased stress level. Increased age and experience of HCWs are significantly correlated with increased stress level. Having personal protection equipment reduced anxiety and depression and increased the resilience of the participants (p>0.05). The predictors of the main variables were varied in the study. Conclusion: Frontline HCWs involved in treating patients with COVID-19 are liable to have a high level of stress that is associated with an increased anxiety and depression level. These high levels affect their mental well-being and resilience. Healthcare institutions in Jordan must tailor appropriate psychological interventions and support that are congruent with HCWs’ needs during and after caring for COVID-19 patients.